Strateji Öğretiminde Kullanılan Farklı Yaklaşımların Öğrencilerin Okuma Stratejileri Üstbilişsel Farkındalık Becerilerine Etkisi - (:unkn) unknown (My University, 2021)
Çalışmanın amacı, strateji öğretiminde kullanılan farklı yaklaşımlarla öğrencilerin okuma stratejileri bilişsel farkındalık becerileri arasında nasıl bir ilişki olduğunu belirlemektir. Araştırmada 6. sınıf düzeyinde 2 deney ve 1 kontrol grubuyla çalışılmıştır. 1. grupta öğretmenin “rehber”; 2. grupta öğretmenin stratejileri açıklayarak “model” olduğu açık strateji öğretim yaklaşımları benimsenmiştir. Deney gruplarında strateji öğretiminde, bütüncül okuma stratejileri kullanılmıştır. Kontrol grubunda stratejiler öğretmen rehberliğinde örtük bir yaklaşımla ve birbirinden bağımsız olarak öğretilmiştir. Araştırmanın modeli kısmen karma sıralı baskın statülü tasarımdır. Örneklem ölçüt örneklemeyle belirlenmiştir. Deneysel süreçte 95 öğrenci, nitel süreçte 32 öğrenciyle çalışılmıştır. Uygulama 10 hafta sürmüştür. Veriler, “Okuma Stratejileri Üstbilişsel Farkındalık Envanteri (MARSI)” ve yarı yapılandırılmış görüşme formuyla toplanmıştır. Analizler SPSS 22 ve MAXQDA 12 programıyla yapılmıştır. Açık strateji öğretimi yaklaşımının ve bütüncül okuma stratejilerinin kullanıldığı, öğretmenin stratejileri açıklayarak “model” ve “rehber” olduğu deney gruplarında öğrencilerin okuma stratejileri bilişsel farkındalık becerilerinde farklılaşma olurken; stratejilerin örtük yaklaşımla öğretmen rehberliğinde ve bağımsız olarak öğretildiği kontrol grubunda farklılaşma gerçekleşmemiştir. Nitel veriler de nicel verileri desteklemektedir.

The purpose of the study was to determine the relationship between different approaches used in strategy teaching and students’ reading strategies metacognitive awareness. Two experimental groups and a control group were used at the 6th grade level in the study. In Group 1 the teacher acted as the "guide"; in Group 2 the explicit strategy teaching approach in which the teacher explained strategy use and acted as the "model" was adopted. Holistic reading strategies were used in the experimental groups. In the control group, strategies were taught under teacher guidance using an implicit approach and independently of each other. The study employed a partially mixed sequential dominant status design. Sampling was determined by criterion sampling. 95 students participated in the experimental phase of the study and 32 students participated in the qualitative phase. The implementation lasted 10 weeks. The data were collected using the "Metacognitive Awareness of Reading Strategies Inventory (MARSI)" and a semi-structured interview form. SPSS v. 22 and MAXQDA 12 software were used for data analysis. In the experimental groups in which the explicit strategy teaching approach and holistic reading strategies were used and teachers explained the strategies and modeled them or acted as the guide, a significant difference was observed in the students’ reading strategies metacognitive awareness skills. No significant difference was observed in the control group in which strategies were taught with an implicit approach under the guidance of the teacher and independently of each other. The qualitative data also supported these quantitative findings.
The Effects of Different Approaches Used in Strategy Teaching on Students' Reading Strategies Metacognitive Awareness Skills